Statin for mood and inflammation among adult patients with major depressive disorder: an updated meta-analysis - Xiao, Xue; Deng, Hu; Li, Peng; Sun, Jifei; Tian, Jing (Frontiers in Psychiatry, 2023)
Introduction Several small sample-sized clinical trials have demonstrated a beneficial effect of statin on depressive mood among major depressive disorder (MDD) patients. However, observational studies have showed the increased risk of anxiety/depression with statin treatment. Therefore, we aimed to evaluate the effects of statin on depressive mood and inflammation status among MDD patients. Methods We performed an updated meta-analysis RCTs identified in systematic searches of PubMed, Cochrane library, Embase, ClinicalTrials.gov, CNKI, Wan fang, VIP and SinoMed database (up to August 2023). The primary endpoint was the Hamilton depression rating scale (HDRS). The secondary endpoints were rate of response to treatment, remission rate, levels of C-reactive protein (CRP), cognition and blood lipid. We evaluated the certainty of the evidence using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) approach. Results The search identified seven RCTs involving 448 patients with a median follow-up of 10.4 weeks (range, 6–12 weeks). Compared with selective serotonin reuptake inhibitors (SSRIs) alone, treatment with statin plus SSRIs was associated with a significantly decreased HDRS (mean difference (MD) = -2.79; 95% confidence interval (CI): -3.83 to -1.76) and C-reactive protein (MD=-0.42 mg/L; 95%CI: -0.53 to -0.12 mg/L), and decreased levels of lipid profiles (P < 0.05). Moreover, statin plus SSRIs was associated with a comparable rate of treatment response (relative risk (RR) = 1.26; 95% CI: 0.98 to 1.62), remission rate (RR=1.33; 95% CI: 0.89 to 1.99). Meta-regression indicated that the follow-up period was a source of heterogeneity regarding the HDRS (r = 0.302, P = 0.041). The quality of evidence was rated as moderate for HDRS and response rate according to the GRADE. Conclusions Statin could safely and effectively improve the symptoms of depression and inflammation status among MDD patients.